MENINJAU KEMBALI GAGASAN PLURALISME KONSTITUSI DI TENGAH KRISIS KONSTITUSIONALISME MODERN: PROSPEK PENERAPANNYA BAGI INDONESIA - Mario Angkawidjaja (Mimbar Hukum, 2023)
Abstract Modern constitutionalism that is trapped in methodological nationalism and overly focused on limiting political power has hindered the development of constitutionalism in responding to contemporary constitutional issues. Modern society, which is becoming increasingly functionally differentiated, has successfully formed various autonomous social subsystems. However, uncontrolled autonomy of social subsystems can give rise to catastrophes that threaten the existence of other subsystems, such as the monetization of media institutions and the politicization of scientific institutions. Using a socio-historical approach and the assistance of systems theory, this paper attempts to re-examine the idea of constitutional pluralism that has the potential to address the crisis of modern constitutionalism. This paper claims that the constitution should not be narrowly understood as an instrument that constitutes and limits political power exercised by the state. Instead, it should be broadly understood as an instrument that can also constitutes and limits the dynamics of other communication media outside of political power. Each autonomous social subsystem can self-regulation and self- limitation without relying on state law. The state should not ignore the condition of functional differentiation or intervene in the autonomy of various subsystems in society. Abstrak Konstitusionalisme modern yang terjebak pada nasionalisme metodologis dan terlalu fokus pada pembatasan kekuasaan politik telah menghalangi perkembangan konstitusionalisme untuk merespons isu konstitusional kontemporer. Masyarakat modern yang semakin terdiferensiasi secara fungsional telah berhasil membentuk bermacam sub-sistem sosial yang otonom. Akan tetapi, otonomi sub-sistem sosial yang tidak terkontrol dapat melahirkan katastrofe yang mengancam eksistensi sub-sistem yang lain, seperti monetisasi institusi media dan politisasi institusi sains. Dengan menggunakan pendekatan sosio-historis dan bantuan dari teori sistem, tulisan ini berupaya untuk meninjau ulang ide pluralisme konstitusi yang memiliki prospek untuk menjawab krisis konstitusionalisme modern. Tulisan ini mengklaim bahwa konstitusi tidak semestinya dimaknai secara sempit sebagai instrumen yang membentuk dan melimitasi kekuasaan politik yang dijalankan oleh negara. Melainkan, perlu dimaknai secara luas sebagai instrumen yang juga dapat membentuk dan melimitasi dinamika medium komunikasi lainnya di luar kekuasaan politik. Setiap sub-sistem sosial yang otonom mempunyai kemampuan untuk meregulasi dan membatasi diri tanpa perlu bergantung pada hukum negara. Negara tidak semestinya mengabaikan kondisi diferensiasi fungsional maupun mengintervensi otonomi berbagai sub-sistem di masyarakat.